Shaping extended product design and development with predictive maintenance capability for digital servitisation - Shi, Tianlan; Ompusunggu, Agusmian Partogi (Elsevier, 2024)
Traditional business models of selling a product as a single item can no longer satisfy the growing service-oriented needs of customers. Service-oriented business models, like servitisation or product-service systems (PSS), have been introduced to respond to this market demand. Predictive maintenance (PdM) strategy is regarded as a key element in the development of such business models because of its effective role in maximising the availability and usability of products. The PdM strategy requires technologies including, sensing, data acquisition, data analytics algorithms and decision support tools. In traditional business models, these technologies are typically developed by third parties when products are already commissioned or in service, which is sub-optimal. It can be argued that PdM technologies developed by original equipment manufacturers (OEMs) can significantly reduce development costs and increase competitiveness. This paper proposes a new framework for guiding OEMs to develop and integrate relevant PdM technologies during the development of new products in support of their new journey in a digital servitisation business model. This encompasses the full life cycle of the product from customers’ needs/values analysis to after-sales service. The model-based system engineering (MBSE) approach was adopted to implement the proposed framework using the selected system modelling language (SysML) tool, namely Capella, and to verify it in an industrial case study.
Keywords: 4014 Manufacturing engineering; Extended products; Product Service Systems (PSS); Servitisation; Predictive maintenance; MBSE; SysML; Analytic Hierarchy Process (AHP)